Cannabis-Based Products for the Treatment of Skin Inflammatory Diseases: A Timely Review - Ana M. Martins; Ana L. Gomes; Inês Vilas Boas; Joana Marto; Helena M. Ribeiro (MDPI AG, 2022)
The use of natural products in dermatology is increasingly being pursued due to sustainability and ecological issues, and as a possible way to improve the therapeutic outcome of chronic skin diseases, relieving the burden for both patients and healthcare systems. The legalization of cannabis by a growing number of countries has opened the way for researching the use of cannabinoids in therapeutic topical formulations. Cannabinoids are a diverse class of pharmacologically active compounds produced by Cannabis sativa (phytocannabinoids) and similar molecules (endocannabinoids, synthetic cannabinoids). Humans possess an endocannabinoid system involved in the regulation of several physiological processes, which includes naturally-produced endocannabinoids, and proteins involved in their transport, synthesis and degradation. The modulation of the endocannabinoid system is a promising therapeutic target for multiple diseases, including vascular, mental and neurodegenerative disorders. However, due to the complex nature of this system and its crosstalk with other biological systems, the development of novel target drugs is an ongoing challenging task. The discovery of a skin endocannabinoid system and its role in maintaining skin homeostasis, alongside the anti-inflammatory actions of cannabinoids, has raised interest in their use for the treatment of skin inflammatory diseases, which is the focus of this review. Oral treatments are only effective at high doses, having considerable adverse effects; thus, research into plant-based or synthetic cannabinoids that can be incorporated into high-quality, safe topical products for the treatment of inflammatory skin conditions is timely. Previous studies revealed that such products are usually well tolerated and showed promising results for example in the treatment of atopic dermatitis, psoriasis, and contact dermatitis. However, further controlled human clinical trials are needed to fully unravel the potential of these compounds, and the possible side effects associated with their topical use.